Sterilisasi Komersial Cassava Chunk pada Kemasan Hermetis Standing Pouch dan Perubahan Sifat Fisikokimianya - Dewi Sartika Saragih; Dede Robiatul Adawiyah; Fransisca Zakaria Rungkat (Institut Pertanian Bogor, 2021)
People’s lifestyles nowdays tend to want healthy-practical food that is strongly supported by a healthy diet. Cassava as whole food is considered as a healthy food and has the potential to become rice substitute but needs an appropriate technology to facilitate food serving. In this research, ready-to-eat cassava products then called